2018
DOI: 10.7763/ijcte.2018.v10.1225
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Decision Support Framework for Health Beverage Flavouring for the Ageing Society Using Artificial Neural Network

Abstract: The objective of this research is to select health beverage flavour appropriate for the ageing people with the aid of a decision support framework by using the artificial neural network. The decision support framework's role is to gather information between consumers and manufacturers. The framework has the capability to compile the collected data and form the suitable model for selecting beverage flavouring of the products. In order to identify the preference of consumer, the artificial neural network has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Juszczyk et al (2018) suggested the capacity to receive information in the automated training process of neural networks and apply it to calculate sports field construction expenses. Kengpol et al (2018) explained that the capability of the ANN has the advantage of predicting data that have never been seen before in the learning process. The ANN is one of the techniques used to solve non-linear problems, which necessitates computing intelligence.…”
Section: Nhmentioning
confidence: 99%
“…Juszczyk et al (2018) suggested the capacity to receive information in the automated training process of neural networks and apply it to calculate sports field construction expenses. Kengpol et al (2018) explained that the capability of the ANN has the advantage of predicting data that have never been seen before in the learning process. The ANN is one of the techniques used to solve non-linear problems, which necessitates computing intelligence.…”
Section: Nhmentioning
confidence: 99%